Inverse Translation as a Pedagogical Tool in the English for Specific Purposes (ESP) Classroom - Cerezo Herrero, Enrique; Pérez-Sabater, Carmen (International Journal of English Studies, 2024)
The aim of this paper is to analyse the potential of inverse translation as a pedagogical tool in the promotion of written expression skills in the English for Specific Purposes (ESP) classroom. Nowadays, we are witnessing a renaissance of translation in teaching practice. As a result, the number of studies trying to delineate the scope of translation in current FLT contexts has proliferated in the last two decades. With a view to adding to the existing literature, we have carried out a longitudinal study, for which a series of translations have been completed during a language course. A pre-study and post-study questionnaire have also been administered in order to gauge the participants’ perspective regarding the use of translation in the language classroom. The results showcase that translation has been extremely beneficial in terms of enhancing written expression, drawing the students’ attention to certain recurring mistakes, and creating metalinguistic awareness.